2021
DOI: 10.1037/rep0000398
|View full text |Cite
|
Sign up to set email alerts
|

Attachment avoidance and health-related quality of life: Mediating effects of avoidant coping and health self-efficacy in a rehabilitation sample.

Abstract: Purpose/Objective: The onset of chronic illness or disability (CID) can be conceptualized as a threat that activates the attachment system. Moreover, the waxing-and-waning nature of CIDrelated symptoms and management of acute and chronic illness stressors means that the attachment system may be repeatedly activated. Contending with repeated threats to health (i.e., security) can complicate psychosocial adjustment to CID and can negatively impact health-related quality of life (HRQoL). Adjustment to CID require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 94 publications
0
9
0
Order By: Relevance
“…Together, these factors might contribute to lower health satisfaction among insecurely-and particularly anxiously-attached individuals. Regarding more avoidantly-attached people, health satisfaction might be less negatively colored by their attachment because of their deactivating regulation processes (Mikulincer & Shaver, 2007) and avoidant coping style (Maras et al, 2021). Specifically, it was found in previous research that more avoidantly attached individuals close off the experience of negative emotions and emotionally disengage and cognitively distance themselves from threatening events (Mikulincer & Shaver, 2019).…”
Section: Health Satisfaction and Health Goal Importancementioning
confidence: 94%
See 2 more Smart Citations
“…Together, these factors might contribute to lower health satisfaction among insecurely-and particularly anxiously-attached individuals. Regarding more avoidantly-attached people, health satisfaction might be less negatively colored by their attachment because of their deactivating regulation processes (Mikulincer & Shaver, 2007) and avoidant coping style (Maras et al, 2021). Specifically, it was found in previous research that more avoidantly attached individuals close off the experience of negative emotions and emotionally disengage and cognitively distance themselves from threatening events (Mikulincer & Shaver, 2019).…”
Section: Health Satisfaction and Health Goal Importancementioning
confidence: 94%
“…Conversely, attachment insecurity-represented by both the avoidance and anxiety dimensions-has been associated with adverse health in previous studies (Brazeau & Chopik, 2020). For instance, research has found that more avoidant individuals tend to report lower health-related quality of life (Maras et al, 2021) and that more anxious individuals tend to report more cardiovascular conditions .…”
Section: Cross-sectional and Longitudinal Associations Between Romant...mentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, highly avoidant individuals with their positive self-image avoid seeing personal weaknesses, and may thus present higher self-efficacy [ 48 , 49 ]. However, the empirical evidence for this relationship is inconclusive as attachment anxiety and avoidance were found to predict poorer self-efficacy among some populations [ 50 53 ] yet not among others [ 54 ].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have demonstrated that attachment insecurity relates to poorer rehabilitation outcomes in chronic pain (Kowal et al, 2015), cancer (Adellund Holt, Jensen, Gilsa Hansen, Elklit, & Mogensen, 2016), and cardiac patients (Heenan, Greenman, Tassé, Zachariades, & Tulloch, 2020). There is also some evidence suggesting that higher attachment avoidance is related to poorer HRQoL in a mixed-CID rehabilitation sample (Maras, Balfour, Lefebvre, & Tasca, 2021).…”
Section: Introductionmentioning
confidence: 99%